Complete mitochondrial genome of a sea cucumber, Euapta godeffroyi (Echinodermata, Holothuroidea, Apodida, Synaptidae). Issue 8 (3rd August 2022) - Ogawa, Akito; Hiruta, Shimpei F.; Aung, Mu Mu; Fujita, Toshihiko
Abstract: We determined the complete mitochondrial genome sequence of a holothurian Euapta godeffroyi belonging to the order Apodida. The complete mitogenome of E. godeffroyi was 16, 410 bp in length and consisted of 13 protein-coding genes (PCGs), two ribosomal RNA genes, and 22 transfer RNA genes. The orders of PCGs and rRNAs did not match those of any recorded holothurian mitogenomes. The maximum likelihood (ML) phylogenetic tree placed E. godeffroyi as the sister group to chiridotid species and supported the monophyly of the order Apodida.